Barriers to the implementation of 4PL in developing countries - Mujthaba Ahtamad; Medet Akhsanov (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Fourth-Party Logistics (4PL) involves sharing non-core activities with an external service provider, which can bring about a variety of benefits for the outsourcer. However, there can be a variety of constraints identified from the mini-cases e.g., stagnant management, resistance to change, and a lack of knowledge. These barriers may have a greater weighting if the 4PL concept is implemented in an emerging economy. Therefore, it is crucial to identify which barriers are present for adopting 4PL in developing countries, and then to consider initiatives to overcome these. Methodology: First, a literature review containing best practices of 4PL in countries across Asia and Europe is presented. Qualitative findings through a series of interviews with specialists were analysed, discussed, and compared with recommendations/existing practices from other developing countries, and then were cross-checked by a specialist using 4PL in Europe. Findings: As a result of our interviews, we identified several managerial barriers in the implementation of the 4PL concept. Originality: The literature review has shown that there is a lack of qualitative research regarding the use of 4PL in developing countries. Therefore, the impact of the results of this paper can be vital for academic knowledge. First
urn:nbn:de:gbv:830-882.0162347; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; HICL and Practice; Excellence in Logistics and Supply Chain Management